STUDI EKSPERIMEN PENGGUNAAN VARIASI AGREGAT BANTAK (MERAPI) DAN MATERIAL LOKAL MENGGUNAKAN BITUMEN SHELL (SINGAPORE)PADA LALU LINTAS BERAT - Endaryanta - (Universitas Negeri Yogyakarta, 2014)
Road engineering is one of the main problem in this country. Rigid pavement frequently defective before load capacity of performance exceeded. Necessary innovation so that the use of material obtained bituminous materialas have good performance. This research caried out of Bantak Merapi as Main materials, combined with local materials Progo and shell Singapore as cementitious materials on flexible pavement to weight load. The Research method used is experiment laboratory with 3 (three) varians (Bantak 100%; Bantak coarse agregat; fine and filler agregat from Progo; coarse and fine agregate Progo; and bantak as filler), each varians consist of 15 samples. Variation of cementitious bitumen are 5%; 5,5%; 6%; and 7% respectively. All specimen have been tested using Marshall laboratory test (dencity; stability; flow; Void in Mix (VIM); Void Filled Bitumen (VFB); Void in Mineral Agregate (VMA); and Marshall Quotient (MQ). Test result showed that values of density; stability; flow; Void In Mix (VIM); Void Filled Bitumen (VFB); Void Minerals Agregat (VMA) and Marshall Quotient were the results 2.16gr/cc; 1230,4kg; 3,42mm; 8,19%; 46,2%; 15,3% dan 376,2 kg/mm respectively. The effective of proportion mix for flexible pavement are Bantak coarse agregate, fine and filler Progo (based on flow values, Void filled bitumen and Marshall Quotient).Kata kunci: Aspal, Bantak, Merapi, Marshall.